Genomic testing in high-grade serous ovarian cancer: current options and future development. Issue 3 (6th March 2023) - Devlin, Michael-John; Miller, Rowan
Abstract : Understanding the genomic complexity of high-grade serous ovarian cancer is now essential in guiding patient management, particularly in the first-line setting. Our knowledge in this area has expanded rapidly in recent years, with biomarkers developing in parallel to agents designed to exploit cancer-associated genetic aberrations. In this review we will take stock of the current landscape of genetic testing and look towards the future with developments that aim to refine personalized treatment paradigms and track treatment resistance in real time.